Developing Coping Strategies Through Rhythmic Physical Activity Among Children with Mild Intellectual Disability to Enhance Sociability - M. Mary Glory Ponrani; Dilshith Azeezul Kabeer; Vinolia B; Vinu W. (Journal of Indian Association for Child and Adolescent Mental Health, 2026)
Background: Children with mild intellectual disability (ID) tend to have problems with emotional regulation, neuromotor responsiveness, and social functioning. Rhythmic physical activity (RPA) is a structured movement with auditory feedback that has demonstrated the possibility to improve developmental outcomes in neurodiverse populations. Objectives: The purpose of this study was to investigate the impact of a 16-week RPA intervention on coping skills, reaction time (RT), and sociability in children with mild ID. Materials and Methods: A quasi-experimental pre-test post-test control group was used with a sample of 30 participants (12–16 years old) divided into experimental ( n = 15) and control ( n = 15) groups. The intervention was to be performed twice a week; each session took 60–70 minutes. Outcome measures were coping skills (KidCOPE-P), RT (Simple Visual RT Test), and sociability (Vineland Social Maturity Scale). One-way analysis of variance was used to analyze the data. Results: There were no notable differences among groups at baseline. After the intervention, the experimental group showed significant improvement in coping skills, RT, and sociability, and no change was observed in the control group. Conclusion: The results indicate that structured RPA is a promising multidimensional intervention to improve emotional regulation, neuromotor performance, and social functioning of children with mild ID. The introduction of RPA into education and treatment can provide a viable means of promoting the holistic growth of this group.